Implementation of Concept Mapping Learning Model to Improve History Learning Achievement - Ariyanto, Eka Nofri; Suyanti, Suyanti (Universitas Negeri Padang, 2023)
This study aims to determine the application and determine the improvement of students' history learning achievement and the obstacles faced in the application of the Concept Mapping model. This research used CAR (Classroom Action Research) with qualitative and quantitative approaches consisting of 3 cycles. The results showed that the application of the Concept Mapping learning model combined with group discussions, quiz games, and the provision of material handouts can improve learning achievement In cycle I student achievement increased by 0.96, cycle II increased by 1.66, and in cycle III increased by 3.30. The obstacles faced in the application of the Concept Mapping learning model are at the beginning of the application of the Concept Mapping learning model there are still some students having difficulty determining secondary ideas. The condition of the lesson at the last hour requires the teacher to create an interesting atmosphere. There must be clear communication between teachers and students because the learning model requires steps to be taken to create Concept Mapping.